Simulation of conductive‐convective heat transfer in a natural basin - Vaitiekūnas, Petras; Katinas, Vladislovas; Markevičius, Antanas (Journal of Environmental Engineering and Landscape Management, 2004)
The state of water flow has been modelled numerically by a three‐dimensional method of a complex investigation of heat and mass transfer. This allows examining interaction of some transfer processes in a natural cooling basin (the Drūkšiai lake): variable density of water, heat conduction in water‐air interface, direct and diffuse solar radiation. Combined effect of these natural actions determines the heat amount that the basin is able to dissipate to the surrounding atmospheric media in thermal equilibrium (no change in the mean water temperature). Mathematical model is simplified ignoring transient derivatives in transfer equations, and time as a variable is included in relaxation coefficients for outer iterations. Full time of calculations using this simulation mechanism for this variable is about 6 h. Basing on water stream velocity and mean temperature profiles measured in the cooling pond as well as on their time variations, suggestions are made that the mixing rate in water is caused by natural and forced convection. Comparison of experimental and numerical results showed a qualitative agreement. For a better quantitative approximation, it is necessary to have more boundary conditions variable with time and to solve unsteady set equations for transfer processes. Šilumos laidumo-konvekcinių mainų natūraliame baseine modeliavimas Santrauka. Matematinis vandens srauto modelis sudarytas skaitiniam trimačių pernašos procesų vienfaziame fluide modeliavimui. Nagrinėjama įvairių veiksnių bei jų sąveikos įtaka pernašos procesams, masės ir šilumos mainams natūriniame baseine‐aušintuve: vandens tankio priklausomybė nuo temperatūros, konvekcija‐laidumas vandens masėje, šilumos laidumo mainai su oro aplinka, tiesioginė ir sklaidžioji saulės spinduliuotė. Matematinis modelis supaprastintas atmetant nenuostovumo narius pernašos lygtyse, laiko kintamąjį įvedant kaip išorinių iteracijų relaksacijos koeficientus. Skaičiavimo trukmė – apie 6 h. Palyginus eksperimentinius ir teorinius rezultatus paaiškėjo kokybinis jų sutapimas. Kad kiekybiniai rezultatai sutaptų tiksliau, reikėtų turėti daugiau įvairių veiksnių ribinių sąlygų, kintančių laike, bei spręsti nenuostoviąsias pernašos lygtis. Reikšminiai žodžiai: hidrodinamika, skaičiuojamoji fluidų dinamika, skaitinis modeliavimas, trimačiai procesai, vienfaziai srautai, baseinas‐aušintuvas, šilumos mainai. First Published Online: 14 Oct 2010